Older people's perception of their readiness for discharge and postdischarge use of community support and services. (7th February 2012) - Coffey, Alice; McCarthy, Geraldine M.
<x xml:space="preserve">Abstract</x> coffey a. & mccarthy g.m. (2013) Older people's perception of their readiness for discharge and postdischarge use of community support and services. International Journal of Older People Nursing8, 104–115 doi: 10.1111/j.1748‐3743.2012.00316.x Aim. To examine older patients perception of their readiness for discharge from hospital to home and use of community supports postdischarge, including readmission. Background. Early discharge leaves little time for older people, families and professionals to prepare. The perspectives of patients are essential to therapeutic caring; however, few studies have examined patient's perception of their readiness for discharge. Design. A quantitative, descriptive and correlational design was used. Data were collected from older patients (n = 335) at discharge and postdischarge using the Readiness for Discharge Scale (Weiss & Piacentine; Journal of Nursing Measurement, 14, 2006, 163) and a Demographic and Community Resource Questionnaire. Findings. At 6 weeks postdischarge, almost one‐quarter had been readmitted. Family support had increased, yet a minimal increase in formal services was found. At discharge, differences in readiness existed between the younger and older old. Significant relationships existed between lower perception of readiness at discharge and increased use of informal and formal support post‐discharge. Lower perception of readiness had a significant relationship with readmission in the older old. Conclusions. Perceptions of readiness reflect the patient's reality and may be significant to discharge preparation and arrangements for support. Implications for practice. Older patients' perspectives should be included in discharge decisions and in individualised approaches by nurses to discharge preparation.